Problems, Needs, and Useful Strategies in Older Adults Self-Managing Epilepsy: Implications for Patient Education and Future Intervention Programs - Miller, Wendy R. (Epilepsy Behav, 2013)
OBJECTIVE: The purpose of this study was to determine, in a sample of older adults diagnosed with epilepsy, perceived self-management problems and needs encountered since diagnosis, as well as strategies used to address problems and needs. METHODS: Qualitative description was used. 20 older adults engaged in face-to-face interviews. Interviews were analyzed via content analysis. RESULTS: Participants reported problems, needs, and strategies in six categories: Information, Physical and Emotional Symptoms, Memory and Concentration, Medications, Commitments, and Relationships. CONCLUSION: Participants noted some problems and needs previously documented in the literature, though current results have built upon extant literature to reveal etiologies of and contexts surrounding problems and needs; new findings were also revealed. This knowledge can be used by health care providers in counseling and educating older adults with epilepsy, and can inform formal self-management interventions. PRACTICE IMPLICATIONS: Determining needs from the patient’s perspective is consistent with today’s focus on patient-centered care. Current findings have led to an organizing framework for problems and needs of older adults with epilepsy. More research is needed to develop the framework so that it can serve as a template for an intervention. In the interim, findings can inform educational practices of those caring for this population.